An experimental study on the oxidation kinetics characterization of broken coal under stress loading. (1st March 2021) - Chao, Jiangkun; Chu, Tingxiang; Yu, Minggao; Han, Xuefeng; Hu, Daimin; Liu, Wei; Yang, Xinlei
Highlights: The oxidation experiment of coal under axial stress of 0–15 MPa was conducted. The coal with axial stress of 9 MPa has the strongest chemical activity. The effect of the axial stress on the spontaneous combustion of coal was investigated. The spontaneous combustion tendency of broken coal under stress conditions was analyzed. Abstract: As mines continue to extend deeper, the stress and ground temperature of the residual coal in the goaf are increased, and the degree of coal rock fragmentation also increases, making the spontaneous combustion of coal more prominent. In this paper, a low-temperature oxidation experiment of coal under axial stress loading conditions was conducted. By analysing the outlet gas flow rate, oxidizing gas derivatives, oxygen consumption rate, heat release intensity, apparent activation energy and other parameters, we studied the effect of axial stress variations on the spontaneous combustion of coal. The results showed that, in an experiment of heating oxidation with the same axial stress, the flow rate of gas generated by the oxidation in the coal sample room gradually decreased with an increasing temperature; at the same temperature, the flow rate of the outlet gas decreased as the axial stress increased. At a low temperature, as the axial stress increased, the rate of oxygen consumption and the amount of derived gas in the reaction system both increased, and the activation energy decreased. When the temperature reached the critical temperature and continuously increased, with an increase in the axial stress, the oxygen consumption rate, heat release intensity and the amount of derived gas in the reaction system first increased and then decreased. Moreover, the temperature point of ethylene gas produced by oxidation was advanced. The effect of the axial stress on the spontaneous combustion of coal was obtained, and the increase in the axial stress first promoted and then suppressed the spontaneous combustion of broken coal.